(untitled) (Research, Society and Development, 2022)
The change from face-to-face teaching methods to remote teaching since the beginning of the restriction measures due to the COVID-19 pandemic required, in the field of education, the sudden adaptation of educators, students and parents for the assurance of teaching continuity and mainly the adjustment, by teachers, of pedagogical activities and teaching strategies in the promotion of learning during the COVID-19 pandemic. Thus, the aim of this study is to analyze the difficulties encountered by teachers in remote teaching during the COVID-19 pandemic. In this process, educators, inevitably faced specific difficulties and obstacles in the institutions, in addition, inadequate technological infrastructure of some institutions and difficulties of access by many students, can be considered another factor. These factors are an obstacle to the success of the implemented remote teaching, because the changes occurred with remote teaching, online learning, the difficulties encountered may reflect in face-to-face teaching, requiring from teachers and students a more significant adaptation in new or unusual teaching practices for teachers and students that, taken together, indicate some renewal of education during and after the pandemic.